Structural properties of charged dust particles with dipole moments - Молдабеков, Ж.А.; Рамазанов, Т.С.; Габдуллин, А.Ж. (Recent Contributions to Physics, 2016)
Molecular dynamics simulation of a two-dimensional system of charged dust particles was carried out in view of the dipole moments. As it is known, in gas discharge the dust particle and ions focused by the dust grain can be considered as a one compound particle with non-zero dipole moment. Notice that in general dusty plasma, which consists of electrons, ions and neutral atoms, is three-dimensional. However, the movement of dust particles is limited to two-dimensional plane.The influence of non-zero dipole moment on the structural properties of the system was analyzed on the basis of the pair correlation function. Possible experimental observation of dipole interaction between dust particles and that of the measurement of dust particles the dipole moment of the complex plasma are discussed in the gas discharge.